LEGALITAS DAN AKIBAT HUKUM KEDUDUKAN ANAK YANG LAHIR DARI PERKAWINAN SIRI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUKOHARJO - Monica Putri Maharani; Anjar Sri Ciptorukmi Nugraheni (Sekolah Tinggi Pariwisata Mataram, 2021)
This article aims to determine and analyze the application process for the issuance of birth certificates for children from unregistered marriages at the Department of Population and Civil Registration of Sukoharjo Regency and to find out and analyze the legal consequences of unregistered Marriage on the application process for issuing birth certificates for children at the Department of Population and Civil Registration of Sukoharjo Regency. This research is a descriptive empirical legal research. Data is obtained from primary data and secondary data with qualitative data analysis techniques. Based on the results of the research and discussion, the conclusion is that the Department of Population and Civil Registration of Sukoharjo Regency is carried out by two methods, namely the application of an Absolute Responsibility Statement (SPTJM) for unregistered marriages that already have a family card or with a Mother's Statement only for unregistered marriages without family cards. As for the legal consequences of siri marriage on the application process for the issuance of a child's birth certificate at the Department of Population and Civil Registration of Sukoharjo Regency, the right of the child that can be granted is only the right to biological recognition without any accompanying civil rights. Whereas the existence of SPTJM does not cause additional legal consequences for the child concerned.